Implementasi Kebijakan Program Pensiun Dini Di PT. Telkom Regional 1 Sumatera - Rizka Dwi Putri; Abdul Kadir; Irwan Nasution (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2019)
The purpose of this study was to determine the implementation of the early retirement program policy at PT Telkom Regional 1 Sumatra. This type of research is qualitative research, triangulation (combined) collection techniques, qualitative inductive data analysis and research results. Research results obtained by researchers that the Implementation of Early Pension Program Policies at PT. Telkom Regional 1 Sumatra through Activities carried out in the early retirement program including socialization, registration, selection, counseling and briefing, and the stages are divided into two parts and in assessing the successful implementation of the George Edward III model there are 4 (four) variables that affect the success or failure of policy implementation, among others, are the factors of communication, resources, disposition and bureaucratic structure. The four variables are interconnected with each other. Based on the results of research and discussion, researchers can conclude that the Implementation of Early Pension Program Policies at PT. Telkom has not been maximized in carrying out an early retirement program, This Can Be Seen From The Stages Passed In Implementing Early Pension Program Policies at PT. Telkom. The conclusion from this study that researchers can conclude that the Implementation of Early Pension Program Policies at PT. Telkom has not been maximized in running an early retirement program.